Pengaruh Kemudahan dan Harga Terhadap Keputusan Pembelian Mahasiswa Secara Online dengan Diskon sebagai Moderasi - Frans Sudirjo; Ikbal; Muhammad Hasan Lubis; Laksono Edhi Lukito; Saddam Hussaen (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
With the increasing development of technology, buying and selling businesses also follow technological development trends by using the internet network. Business people must always understand customer needs in order to attract customers' interest in buying, one of which is always following changes and rapid developments in business tastes. This type of research is quantitative research. This research aims to determine the effect of convenience and price on students' online purchasing decisions with discounts as moderation. The sampling technique in quantitative research is carried out randomly, data collection uses research instruments, statistical data analysis with the aim of testing predetermined hypotheses. The population in this study were students who had shopped online, consisting of 160 respondents. The results of this research found that convenience and price influence students' online purchasing decisions. Discounts as moderation are able to moderate the influence of convenience and price on students' online purchasing decisions.